COLLABORATIVE VIDEO PROJECTS IN EDUCATIONAL CONTEXT: EXPLORING THE OUTPUT OF GRAMMAR LEARNING - Hustiana, Hustiana; Bahtiar, Muflihah; Meiliza, Zuhra (ENGLISH JOURNAL, 2024)
This research endeavored to represent the results of students’ grammar learning as recapitulated in the Collaborative video project. It strived to find out whether students were able to adapt the context of the video content with the usage of grammar itself. This was a qualitative case study research that departed from the results of the researcher’s observations in class where students still have grammar scores below 70 and many students still duplicated sentences from the internet if requested to create a sentence using certain tenses in class. This research method was a descriptive analysis where the researcher transcribed utterances in three randomly selected videos and then categorized them into materials that have been studied in class over fourteen meetings. It was discovered that the three videos used more simple present tense and past tense. Meanwhile, material that never appeared in the video at all were past continuous and past perfect continuous. There were 33 simple present tense utterances in the first video, 18 utterances in the second video, and 6 utterances in the third video. Meanwhile, past tense utterance were 5 sentences in the first video, 9 sentences in the second video, and 6 sentences in the third video. The results of this collaborative video can increase students’ creativity in adapting conditions to the use of grammar and can increase their vocabulary used in grammar. This research can be used as a reference for future researchers who desire to do something comparable by exploring different grammar points. Apart from that, this video projects can be used as a medium for further grammar learning. Keywords: Collaborative Video Project, Educational Context, Grammar Learning